Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
The required expression which can be used to find the nth term in the sequence is:
[tex]a_n=2n+3[/tex]
Hence, the fourth option i.e. 2n+3 is the correct option.
Step-by-step explanation:
Given the sequence
5, 7, 9, 11,...
An arithmetic sequence has a constant difference 'd' and is defined by
[tex]a_n=a_1+\left(n-1\right)d[/tex]
computing the differences of all the adjacent terms
[tex]7-5=2,\:\quad \:9-7=2,\:\quad \:11-9=2[/tex]
The difference between all the adjacent terms is the same and equal to
d = 2
So
- a₁ = 5
- d = 2
Thus, the nth term of the sequence is
[tex]a_n=a_1+\left(n-1\right)d[/tex]
substitute a₁ = 5 and d = 2 in the sequence
[tex]a_n=2\left(n-1\right)+5[/tex]
[tex]a_n=2n+3[/tex]
Therefore, the required expression which can be used to find the nth term in the sequence is:
[tex]a_n=2n+3[/tex]
Hence, the fourth option i.e. 2n+3 is the correct option.
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.